2015
DOI: 10.1017/s002531541500106x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of RBL–2H3 cells degranulation by nitroaromatic compounds from a Bacillus strain associated to the Amazonian sponge Metania reticulata

Abstract: Symbionts in sponges must interact with the host immune system, and this can be mediated by immunomodulators. As the bases of the immune system in sponges resemble those of higher metazoans, it is possible that compounds from this microbiota show similar effects in other phyla. It is also known that several antibiotics, in special macrolides, can modulate many components of the immune response and sponges and their associated microorganisms are a rich source of these compounds. Therefore, we tested the immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Furthermore, bacillus could also produce compounds with anti-bacterial properties. According to Rozas et al (2015) reported the antibacterial activity of Bacillus sp. isolated from the Amazonian freshwater sponge Metania reticulata.…”
Section: Bacillus: Biosurfactant and Its Broad Applicationsmentioning
confidence: 99%
“…Furthermore, bacillus could also produce compounds with anti-bacterial properties. According to Rozas et al (2015) reported the antibacterial activity of Bacillus sp. isolated from the Amazonian freshwater sponge Metania reticulata.…”
Section: Bacillus: Biosurfactant and Its Broad Applicationsmentioning
confidence: 99%
“…Among fourteen bacterial strains isolated from the freshwater sponge Metania reticulata (Bowerbank, 1863) from the Negro River (Brazil), Rozas et al [ 27 ] individuated two bacterial strains (namely, MERETb.761 and MERETb.762) showing antimicrobial activity. Both bacterial strains inhibited the fungus Aspergillus sp., whereas MERETb.762 also inhibited Staphylococcus aureus .…”
Section: Bacterial Isolates From Freshwater Sponges: Description and ...mentioning
confidence: 99%
“…The production of immunosuppressants is commonly considered a bacterial strategy to avoid expulsion from their hosts [ 45 ]. Rozas et al [ 27 ] supposed that MERETb.762 might utilize such a strategy to maintain its relationship with the host. The authors also suggested that performing immunosuppressive assays on isolated compounds could enhance the discovery of novel bioactive molecules.…”
Section: Bacterial Isolates From Freshwater Sponges: Description and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The highest amino acid sequence identity is to NfnB (44%) and CnbA (43%), which are nitroreductases involved in the degradation of nitroaromatic and chlorinated nitroaromatic compounds (Wu et al, 2006;Manina et al, 2010). Sponge holobionts are known producers of various nitroaromatic compounds (Rozas et al, 2016) and Ca. P. multivorans might use the nitroreductase to utilize them as nutrition.…”
Section: Ca P Multivorans Responds To Potentially Holobiontderived Co...mentioning
confidence: 99%